2014
DOI: 10.1017/s0022215114000188
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of diagnostic groups amongst 1034 patients seen in ENT practices for dizziness

Abstract: In this study of patients referred to ENT for dizziness, benign paroxysmal positional vertigo was the dominant diagnostic entity, in all age groups and overall. All clinicians in contact with dizzy patients must consider benign paroxysmal positional vertigo, especially in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
0
21
0
6
Order By: Relevance
“…Meniere-like syndrome is rare in children in our experience (1.1%) compared to 13.8% in adults. 15 Meniere's syndromes associated with vertigo, hypoacousia, and tinnitus with a clogged ear have only been observed in our center since the past 8 years. Perhaps it is an underestimated diagnosis because all the symptoms are not always found during the interview: tinnitus and mild hearing loss are rarely reported spontaneously by the child.…”
Section: Meniere-like Syndromementioning
confidence: 97%
See 1 more Smart Citation
“…Meniere-like syndrome is rare in children in our experience (1.1%) compared to 13.8% in adults. 15 Meniere's syndromes associated with vertigo, hypoacousia, and tinnitus with a clogged ear have only been observed in our center since the past 8 years. Perhaps it is an underestimated diagnosis because all the symptoms are not always found during the interview: tinnitus and mild hearing loss are rarely reported spontaneously by the child.…”
Section: Meniere-like Syndromementioning
confidence: 97%
“…Benign paroxysmal positional vertigo (BPPV; canalolithiasis and cupulolithiasis) is rare in children outside a traumatic context, whereas in adults it is the most frequent diagnosis in patients with no context of cranial trauma (53% of vertigo cases in adults). 15 The clinical picture of nonpositional benign paroxysmal vertigo of childhood (BPVC) is characteristic of young children 2 to 5 years of age but is occasionally reported in older children. However, its prevalence in the literature is variable, ranging from 6 to 20%, probably because of the lack of a strict clinical definition, and also because of their rapid and spontaneous resolution (thus not arriving in specialized clinics).…”
mentioning
confidence: 99%
“…) and is the leading cause of dizziness (Lüscher et al. ). It has been shown that UPVD patients struggle to maintain consistent arm actions during trunk movement without visual information (Raptis et al.…”
Section: Introductionmentioning
confidence: 99%
“…4 The Epley particle repositioning manoeuvre has become the standard treatment for this condition. Hughes and colleagues investigated the number of Epley manoeuvres required for symptom control in BPPV.…”
Section: Focus On Epistaxismentioning
confidence: 99%